Avaliação dos projetos de educação ambiental : estudo de caso em escola do noroeste do Paraná - Dalzotto, Edilaine (2011)
Thinking about environmental education and, above all, insert it into the educational process is a process that fortifies the theoretical foundations of education and works in social awareness. In this sense, it becomes important to evaluate how environmental issues are addressed in education from the perspective of forming conscious individuals to exercise their citizenship. Therefore, this study aims to understand the theoretical and methodological context of environmental education projects developed in a Public School from Northwest of Paraná state, checking factors that influence and underlie the quality of them. The route of this study had a qualitative approach, through observation of teachers in a qualification course and content analysis of interviews and projects undertaken by the college. Made part of this study, students from 5th and 6th grades, and six effective teachers of elementary school science from 5th to 8th grades. The analysis and interpretation of the results showed that the linkage between public policy and environmental education is a constant in all aspects dimensioned in the educational process. It also appears that the projects developed by the school are mostly the ones proposed by the state government and which are characterized as globalizing projects, involving several themes that look to care for social needs, however, it?s noted on these projects, a deficiency of the indicative factors and evaluative discretions required to achieve a reflective educational practice and quality settings that support adjustments and new referrals for those in development and future school projects. In addition, interdisciplinary practices are not applied according to the principles of environmental education, revealing the difficulty in changing teachers pedagogical proposal. Thus, it is responsibility of the teachers and school to propose interdisciplinary projects and to develop an ongoing evaluation process that goes beyond the simplistic evaluation, and is also important that the school promotes conditions for teacher's qualification and application of knowledge in school context.